Prevalence and treatment of perinatal anxiety: diagnostic interview study - Susan Ayers; Andrea Sinesi; Rose Meade; Helen Cheyne; Margaret Maxwell; Catherine Best; Stacey McNicol; Louise R. Williams; Una Hutton; Grace Howard; Judy Shakespeare; Fiona Alderdice; et al. (BJPsych Open)
Background Anxiety affects around one in five women during pregnancy and after birth. However, there is no systematic information on the proportion of women with perinatal anxiety disorders who want or receive treatment.